The influence of defects on the interfacial thermal conductance of β12/χ3 borophene lateral heterostructures - Li, Zhiping; Chen, Lang; Li, Dengfeng (Frontiers in Physics, 2025)
Interfacial thermal transport properties are critical for heat dissipation in micro/nanoelectronic devices. Borophene has structural polymorphism and the lateral heterostructures were often observed. The influence of defect on the interfacial thermal conductance (ITC) of β12/χ3 borophene heterostructures (BHs) was investigated through modified Lennard-Jones potential-based molecular dynamics simulations. The pristine interface exhibits high ITC of 6.57 GW K−1 m−2. The single-vacancy (SV) and doublevacancy (DV) defects at the interface reduced ITC to 3.14 GW K−1 m−2 and 1.57 GW K−1 m−2, respectively. The vibrational density of states (VDOS) overlap analysis shows the opposite trend with the change of ITC. Fortunately, spectral thermal flux and stress distribution can explain the reduction of the ITC for SV-BHs and DV-BHs. The von Mises stress of certain atoms at the interface for DV-BHs reaches up to 40 GPa. SV and DV defects lead to larger stress concentration and stronger phonon scattering near the interface. Defect engineering offers crucial insights into the potential of borophene heterostructures for thermal management.